PENGARUH PENNGGUNAAN STRATEGI PEMBELAJARAN INQUIRY TERHADAP HASIL BELAJAR SEJARAH PADA MATERI POKOK DEMOKERASI DI KELAS XI SMA NEGERI 1 HUTABARGOT - Nur Ainun (Pendidikan Sejarah, 2019)
This study aims to know whether there is a significant influence of using inquiry strategy on students’ history achievement on the topic democracy at the eleventh grade students of SMA negeri 1 Hutabargot. The research was conducted by using experimental method with 60 students as the sample and they were taken by using total sampling technique. Test and observation were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using inquiry strategy was 64,67and (b) the average of students’ democracy achievement before using inquiry strategy was 64.67 (enough category) and after using inquiry strategy was 73.67 (good category). Furthermore, based on inferential statistic by using ttest one tail, the result showed that ttable was less than tobserved (1.68< 2.19), it means, there is a significant influence of using inquiry strategy on students’ history achievement on the topic democracy at the eleventh grade students of SMA negeri 1 Hutabargot.